Development of Hsmar1 transposon tools for research and biotechnology - Bhatt, Shivam (2019)
DNA transposons are mobile genetic elements that relocate between genomic loci. This relocation is termed transposition and is catalysed by an element-encoded enzyme called transposase. Hsmar1 is a DNA transposon that invaded the primate genome ~50 Mya and was active for ~13 My. Over the last decade, the molecular mechanisms of Hsmar1 transposition and autoregulation have been covered extensively. I took advantage of this mechanistic understanding to develop transposon technologies using Hsmar1 as a proof-of-concept platform. In research and biotechnology, transposons are used for insertional mutagenesis, transgenesis, gene therapy and next-generation sequencing. To improve existing transposon tools, I sought to establish increased control over the transposition reaction. Most transposases integrate their transposons semi-randomly throughout the genome. To control where transposons are integrated, I fused the Hsmar1 transposase to a catalytically inactive Cas9 variant, dCas9. The aim was to bias transposon insertions into the vicinity of a pre-determined target site bound by a guide RNA-dCas9-transposase ribonucleoprotein complex. I detected a 14.8-fold enrichment of transposon insertions into a 600 bp target site in an in vitro plasmid-to-plasmid assay compared to unfused transposase. Additionally, I show that 100 % of targeted insertions occur within 22 bp to one side of the guide RNA binding site. Next, I developed a light-inducible transposase for non-invasive, spatio-temporal control over the onset of transposition. Light-activated transposase reached up to 50 % of the activity of wild-type. To find hyperactive transposases, I constructed a library of 2 x 105 transposase mutants. I isolated three hyperactive variants and found that hyperactivity occurs due to faster transposon-end synapsis. Lastly, I developed an Hsmar1 transpososome, which is a pre-assembled synaptic complex in vitro. I show that this complex can be chemically transformed into E. coli for one-step insertional mutagenesis. Furthermore, the transpososome can also be lipofected into human cells, where the level of transposition exceeds that of the traditionally used transposase-helper plasmids.